METODE ABA (APPLIED BEHAVIOR ANALYSIS) UNTUK MENINGKATKAN PEMAHAMAN ANAK AUTIS - Septi Nur Irianti Ramdan; Yahdinil Firda Nadirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Autistic children are children who experience very complex developmental disorders, starting from disorders in language or communication, both verbal and non-verbal, not easily adjusting or changing their routines with their surroundings, doing something repeatedly, to disorders of social interaction. In essence, autistic children also need education like other normal children, because autistic children actually have potential that can be developed. These potentials can be maximized if they get the right treatment. The key to the success of this learning process is determined by several components, including teachers, methods used, and so on. The appropriate method in handling autistic children is the ABA method. This study aims to analyze the Use of the ABA (Applied Behavior Analysis) Method to Improve Understanding of Autistic Children in Learning at SKHN 01 KOTA SERANG. The research approach used is a qualitative descriptive approach. The focus of this study is autistic students at SKHN 01 KOTA SERANG. Data collection techniques include: observation methods, interview methods and documentation methods. Based on the results of research that has been conducted through observation, interviews and documentation, it can be concluded that the use of the ABA (Applied Behavior Analysis) method for students with autism in learning at SKHN 01 Serang City is very appropriate and helpful.